Democratisation of Cinematic Space in Malaysia: Digital Film Activism and the Freedom Film Festival - Ahmad, Mahyuddin; Lee, Yuen Beng; Wang, Lay Kim (Han Chiang College, 2017)
Digital film activism as a popular alternative platform is used for the publication and dissemination of information, ideas, and views deemed too sensitive for the state controlled mainstream media. Such forms of activism have been actively carried out through the annual Freedom Film Festival (FFF). Held since 2003, the FFF exhibits films and documentaries with hopes of spreading justice, peace, equality, and democracy. The FFF exists not only as a site of exhibition and distribution that bypasses state legislation and censorship in delegitimising the oppressive forces of censorship and state control, it also encourages the production of such films that would either be prohibited or subjected to strict cinematic, cultural or political controls. This paper critically examines the development of digital film activism and the FFF along the theoretical formulation of Third Cinema to analyse if indeed cinematic space in Malaysia has begin to become democratised